2017
DOI: 10.5539/ibr.v10n7p178
|View full text |Cite
|
Sign up to set email alerts
|

The Consumer, the Consumed, & the Devastated: A Longitudinal Study of Jordanian Consumers

Abstract: Based on a longitudinal study of a 120 Jordanian housewives, this study examines the influence of the Arab spring events on the Jordanian consumers in the form of the changes in the demographic and consumption patterns of the Jordanian consumers during the years 2012-2017 (i.e. the Arab spring phase). The results of this study reveals significant implications of the events of the region and governmental policies on the Jordanian consumers and presents the first ever typology of Jordanian consumers. Generally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In Jordan, the study of Obeidat (2017), confirmed the impact of demographic, commodity and seller factors, as well as the impact of some external factors in influencing purchasing behavior. Consequently, due to the lack of studies examining consumption behavior and the factors affecting it in Jordan, this study aims to identify the impact of the psychological and social factors of Jordanian households on their purchasing and consumption decisions and at a difficult economic stage.…”
Section: Literature Reviewmentioning
confidence: 91%
See 2 more Smart Citations
“…In Jordan, the study of Obeidat (2017), confirmed the impact of demographic, commodity and seller factors, as well as the impact of some external factors in influencing purchasing behavior. Consequently, due to the lack of studies examining consumption behavior and the factors affecting it in Jordan, this study aims to identify the impact of the psychological and social factors of Jordanian households on their purchasing and consumption decisions and at a difficult economic stage.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Finally, 12.6% of the sample identified the bad customer service provided to them in store as the reasons they refrain from purchase and consumption. This factor was found to largely influence purchase, purchase intentions, and acts of complaining and revenge (Obeidat et al 2017). …”
Section: "One Of the Main Problems We Are Facing In Jordan Is The Conmentioning
confidence: 99%
See 1 more Smart Citation